Reworked marine pythonomorph (Reptilia, Squamata) remains in Late Pleistocene cave deposits in central Spain. (May 2015) - Hontecillas, Daniel; Houssaye, Alexandra; Laplana, César; Sevilla, Paloma; Arsuaga, Juan Luis; Pérez-González, Alfredo; Baquedano, Enrique; Knoll, Fabien
Abstract: Three sites at the Calvero de la Higuera complex (Camino Cave, Navalmaíllo Rock Shelter, and Buena Pinta Cave), near the village of Pinilla del Valle (Madrid, Spain), are known for their record of Neanderthals and other Late Pleistocene mammals. Occasionally, they also yield much more ancient reworked remains, which come from the Upper Cretaceous dolomites and carbonatic sandstones in which these caves and shelters are developed. These are mostly teeth of sharks and rays and vertebrae and teeth of bony fishes, but several reptile vertebrae and teeth have also been found. These reptile remains, which we describe here, likely belong to the pythonomorph incertae sedis Carentonosaurus cf. mineaui . This taxon is known from several outcrops in the southwest of France but is rare on the Iberian Peninsula; indeed, only a few remains possibly related to the genus have been found (in the Cabaña Formation, Asturias, Spain). The pythonomorph remains discussed here are the first fossils of marine reptiles from the Madrid region. Should the assignment to Carentonosaurus be confirmed, the teeth would provide novel data on the characteristics of this rather poorly known taxon, and might help clarify its phylogenetic relationship within Pythonomorpha. Highlights: We study new isolated vertebrae and teeth of a Late Cretaceous marine pythonomorph found as reworked elements at the Late Pleistocene Calvero de la Higuera karstic complex in Madrid (Spain). We establish four morphotypes in teeth according to the position of the carinae and the ornamentation of the crown enamel. We establish two possible morphotypes in teeth according to the slope of the crown apex. The dorsal vertebrae have similar sizes and features to the pythonomorph incertae sedis Carentonosaurus mineaui . The absence of any other fossil reptile material suggests that the teeth found may also belong to Carentonosaurus . If this is confirmed, they will be the first described teeth for this taxon.